FOSTERING LISTENING MATERIAL BASED ON IELTS TEST FOR COLLEGE STUDENTS - Dwi Settya Mahaputri (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Listening skill plays an important not only for communication but also for learning language through comprehensible input. Besides that, listening is a complex process. Students’ in tertiary level of education, which is called college students, faced difficulties in learning it, such as; they cannot identify the key words that they need to listen out for because they are trying to understand every single word, they cannot recognized the intended meaning, and many more. The listening material for college students provides them to be familiar with proficiency test, like IELTS test. Therefore, this research was expected to help the college students to be more comprehended of IELST Listening test. This research was Research and Development (R & D) research. It was aimed to design a new product of listening material based on IELTS test for English Department students of STKIP Yayasan Abdi Pendidikan Payakumbuh. The procedures of this research involved identification of need analysis, writing the course grid, material production, material implementation, material evaluation, material first draft revising and material final draft writing. The findings showed that students need most related to the audio recording are 57% out of 28 students’ need a conversation between two people set in an everyday social situation. 89 % of students need to hear more a monologue set in an everyday social situation. 70% need audio recording of a conversation between up to four people set in an educational or training context. Then, 96 of students’ need to audio recording is about a monologue on an academic subject. Then based on the question types, the students’ need: multiple choice 54%, short answer questions 93%, sentence completion 71%, notes/chart/table completion 96%, labeling diagram 100%, classification 89%, and matching 93%. It was successful in increasing college students interested in listening skill.